Sarothrin from Alkanna orientalis Is an Antimicrobial Agent and Efflux Pump Inhibitor - Bame, Jessica R.; Graf, Tyler N.; Junio, Hiyas A.; Bussey, R. Owen, III; Jarmusch, Scott A.; El-Elimat, Tamam; Falkinham, Joseph O., III; Oberlies, Nicholas H.; Cech, Richard A.; Cech, Nadja B. (Planta Medica, 2013)
An Alkanna orientalis leaf and flower extract inhibited the growth of Staphylococcus aureus, a pathogen that causes an estimated 478 000 hospitalizations in the US annually. Bioassay-guided fractionation of A. orientalis resulted in isolation of the flavonoid sarothrin (5,7,4′-trihydroxy-3,6,8-trimethoxyflavone), which inhibited the growth of Mycobacterium smegmatis (MIC 75 µM) and S. aureus (MIC > 800 µM), and possessed efflux pump inhibitory activity. This is the first report of antimicrobial or efflux pump inhibitory activity of sarothrin, and of its presence in A. orientalis. Our findings suggest that the effectiveness of A. orientalis extracts is due to a combination of multiple constituents, including sarothrin.
Keywords: Alkanna orientalis; Boraginaceae; antimicrobial; efflux inhibition